Traveling Plants: - Francesca Genna (Art&Sensorium: Revista Interdisciplinar Internacional de Artes Visuais)
This body of visual work began during the 2020/21 pandemic, as I explored alternative printing methods closely tied to nature. As an artists residence in my own garden, I focused on weeds and invasive plants, using botanical printing techniques like “eco-printing", which transfers the shapes and colors of plants directly onto paper and textile. Techniques that directly use flowers, leaves and plants to extract colors and images, rediscovered and have become increasingly popular in recent years of research and dissemination of natural methods of self-production on the web. Slow printing processes with also therapeutic value. Rather than traditional drawing, I sought to capture plants and flowers in unexpected ways, embracing the element of surprise. My ongoing work highlights the interplay between natural elements—plants, flowers, seeds—and forces like sunlight and water, where nature itself becomes the material for image creation. Nature, which had always influenced my work, in a quest for knowledge of things through direct observation of the different forms of life, becomes a structural part, the very material of manipulation and transformation, vital energy for the appearance of images. It is no longer an aesthetic or symbolic attitude, but a physical procedure for the realization of the image.